PENGARUH KEPEMILIKAN MANAJERIAL DAN INSTITUSIONAL, ASIMETRI INFORMASI, RISIKO LITIGASI TERHADAP PENERAPAN KONSERVATISMA AKUNTANSI - Nicholas Alexander Tunggal; Lodovicus Lasdi (Universitas Katolik Widya Mandala Surabaya, 2021)
The users of financial statements depend on the financial statements produced by the company in determining decisions related to the company's business processes. The importance of producing competent financial reports can be done with the principle of conservatism which speaks of prudence. This research is conducted by examining several factors that are thought to have an effect on the application of conservatism. Tests were carried out on non-financial companies in the 2017-2019 period on the IDX. The samples taken in this research are 312 samples by purposive sampling. The results of the data that have been collected through the multiple regression test method, namely managerial ownership, institutional ownership and information asymmetry are known to have no positive effect on accounting conservatism, but unlike other variables, litigation risk has a negative effect on the application of conservatism.